Productivity Trends in Indian Foresiry - Mathur, R. S. (Indian Forester, 1976)
The trends in the production of industrial wood, fuel wood and total wood during the years 1949-50 to 1971-72 from the forests of India have been analysed, along with those for total wood production per ha of forest area and per capita of population and for the total annual revenue, expenditure and revenue surplus of the forest departments in the country. A 4 year production cycle in total wood production has been isolated. Some short term forecasts have also been attempted on the basis of regression analyses.